1995
DOI: 10.1002/nme.1620380306
|View full text |Cite
|
Sign up to set email alerts
|

Optimized partitioning of unstructured finite element meshes

Abstract: We address the problem of automatic partitioning of unstructured finite element meshes in the context of parallel numerical algorithms based on domain decomposition. A two-step approach is proposed, which combines a direct partitioning scheme with a non-deterministic procedure of combinatorial optimization. In contrast with previously published experiments with non-deterministic heuristics, the optimization step is shown to produce high-quality decompositions at a reasonable compute cost. We also show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 11 publications
1
29
0
2
Order By: Relevance
“…Typically the cost function used is simply the total weight of cut edges, |E c |, and then the gain expresses the change in |E c |. More recently, however, there has been some debate about the most important quantity to minimize and in [14], Vanderstraeten et al demonstrated that it can be extremely effective to vary the cost function based on a knowledge of the solver. Meanwhile, in [17] we showed that the architecture of the parallel machine and how the partition is mapped down onto its communications network can also play an important role.…”
Section: The Gain and Preference Functionsmentioning
confidence: 97%
“…Typically the cost function used is simply the total weight of cut edges, |E c |, and then the gain expresses the change in |E c |. More recently, however, there has been some debate about the most important quantity to minimize and in [14], Vanderstraeten et al demonstrated that it can be extremely effective to vary the cost function based on a knowledge of the solver. Meanwhile, in [17] we showed that the architecture of the parallel machine and how the partition is mapped down onto its communications network can also play an important role.…”
Section: The Gain and Preference Functionsmentioning
confidence: 97%
“…Vanderstraeten et al (Vanderstraeten and Keunings, 1995;Vanderstraeten et al, 1996) have proposed several two-step mesh partitioning approaches. These approaches first produce a partitioning result via an initial partitioning algorithm.…”
Section: An Iterative Mesh Partitioning Approachmentioning
confidence: 99%
“…They are based on graph partitioning techniques (Pothen, 1997), which have been used extensively for parallel scientific computations. Herein, a finite element mesh is transferred to a Communication Graph (C-Graph), which is similar to the diagonal dual graph used by Vanderstraeten and Keunings (1995), and then partitioned via one of the mesh partitioning packages. Details on the transformation from a finite element mesh to a C-Graph can be found in Hsieh et al (1995).…”
Section: Mesh Partitioningmentioning
confidence: 99%
“…Thus, domain decomposition in DSMC can become very efficient by taking advantage of the success in graph partitioning. Related descriptions and reviews of graph partitioning can be found in Kernighan and Lin (1970), Barnard and Simin (1994), Hendrickson and Leland (1994), Karypis and Kumar (1995), Vanderstraeten and Keunings (1995), Walshaw et al (1995), Vanderstraeten et al (1996) and Robinson (1998), and are not repeated here. There are, however, two graph partitioners available in the public domain worthy of mentioning, and they are described in the following.…”
Section: Introductionmentioning
confidence: 96%